Rancang Bangun Game Edukasi Penyakit Rabies Menggunakan Unity Dengan Metode Game Development Life Cycle - Mulyosaputro, Matthew Alden; Iswari, Ni Made Satvika; Wijaya, I Nyoman Yudi Anggara (JATISI, 2025)
Rabies, which is usually transmitted through dog bites, is one of the common diseases in Indonesia. Based on data from Indonesia Ministry of Health, there were 31,113 cases of rabies animal bites and 11 deaths caused by rabies in 2023. Although efforts to eradicate rabies have been made in Indonesia, it has not been carried out completely due to the lack of public awareness about rabies. Therefore, there needs to be a means that can be used to increase public awareness about rabies. In this study, the author designed and created a game that aims to educate the public about rabies and how to prevent it. The rabies educational game was created using the Game Development Life Cycle method and was created using Unity software. The game produced in this study is a rabies education game in the form of a story-based choice game where the player's choice will impact the player's success in preventing or failing to handle rabies. From the test results, it can be concluded that the rabies education game is able to entertain players and educate players about rabies and how to prevent it.